Students’ Motivation, Self-Esteem, and Study Habits: Interrelationships, Variances, and Implications - Riego de Dios, Erin; Asio, John Mark (Indonesian Journal of Education and Social Sciences, 2026)
Studying at the tertiary level is a critical stage for students. Finishing a college degree is paramount to their life success. Factors such as motivation, self-esteem, and study habits can significantly contribute to success in college. This paper investigates students’ motivation, self-esteem, and study habits at a tertiary education institution. The researchers used a cross-sectional design with correlation methods to determine the interrelationships and variances among the three variables. Using cluster sampling technique, 387 participants voluntarily completed an online survey with the help of Google Form. The data gathering happened during the Second Semester of the Academic Year 2024-2025. Three standardized instruments gathered pertinent data. The analysis included both descriptive (frequency, percentage, mean, and standard deviation) and inferential methods (Mann Whitney U, Kruskal Wallis H, and Spearman’s Rho tests), aided by IBM SPSS version 23 software. The main findings revealed a high degree of motivation and study habits among participants, accompanied by moderate self-esteem. The study also found significant differences in motivation (by year level and GPA) and study habits (by sex and GPA). Finally, there was a low to moderate interrelationship among the variables. The study concluded that variances and interrelationships existed among the three variables. The researchers suggested important implications based on these findings.